Intelligent dynamic load balancer for JBoss application server - Mileff, Péter; Nehéz, Károly (Acta Agraria Kaposváriensis, 2006)
The growth of Internet services during the past few years has increased the demand for scalable distributed computing systems. E-commerce systems concurrently serve many clients that transmit a large, number of requests. An increasingly popular and cost effective technique to improve server performance is load balancing, where hardware and/or software mechanisms decide which server will execute each client request. Load balancing mechanisms distribute client workload equally among server nodes to improve overall system responsiveness. Load balancers have emerged as a powerful new technology to solve this. This paper focuses on a new generation of adaptive/intelligent dynamic load balancing technique, which based on the J2EE technology and can be practical in J2EE application servers. The paper discusses in detail both the theoretical model of the load balancing and its practical realization. The effectiveness of the new balancing method will be demonstrated through exact measurement results compared with former traditional non-adaptive methods.
Keywords: Distributed systems; Adaptive Load Balancing; J2EE Application server; JBoss